A Correlational Study Between Reading Anxiety and Reading Achievement of the Eleventh Grade Students of MA Miftahul Khairiyah Banjarbaru in the Academic Year of 2015/2016. - Ulfini, Niswi; Sutiono, Cayandrawati; Triana, Novita (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
This research aimed to find out the correlation between reading anxiety and reading achievement in senior high school level. The researcher used correlational study as the type of research. The population of this research was the eleventh grade students of Madrasah Aliyah Miftahul Khairiyah Banjarbaru in the academic year of 2015/2016. The number of the population was 53 students. To analyze the data, the researcher used pearson product moment correlation in Statistical Package for Social Science (SPSS) version 21.0. The result showed that that the coefficient correlation between both variables was -0.128. It showed that there was no significant correlation between studentsâ reading anxiety and their reading achievement. It is also found that 18 students belonged to high level reading anxiety, 33 students had moderate level of reading anxiety, and 2 students were categorized into low level. For level of reading achievement, 2 students were in very good category, 21 students were in good category, 23 students had fair reading achievement, and 6 students had bad reading achievement. Though the study found no correlation between the two variables, it still found that reading anxiety existed in senior high school level. Accordingly, it is suggested that the students have to encourage themselves to overcome the anxious feeling that they have when they are reading English in order to make reading comprehension easier for them. It is also suggested to the teachers to give the students more reading strategy in order to overcome their problems causing reading anxiety.